Multi-Sector Collaboration in Legal Protection for Teachers and Students Amidst of Covid-19 Pandemic (Case of Mirit Kebumen, Indonesia) - Surip, Surip; Rasdi, Rasdi; Nadiyya, Ahsana; Arifin, Ridwan; Kurniawan, Dwi Bagus (Faculty of Law, Universitas Negeri Semarang, 2021)
The Covid-19 pandemic has become one of the most unexpected problems, and has had a significant impact on all sectors. Not only the health sector, but also education. The pandemic is forcing all parties to change the pattern and method of education, as well as forcing them to adapt quickly. Various learning process activities are carried out online, but various research results show the weaknesses of this method. Starting from the effectiveness of the learning process, dependence on communication devices (cell phones and laptops), to various legal problems faced by teachers, students, and parents of students. This service program aims to provide reinforcement in terms of protection for teachers and students during the pandemic by involving multi-sectors (Universities-Legal Aid Institutions-Teachers' Union). The partner in this activity is the Indonesian Teachers Association (PGRI) in Mirit District, Kebumen Regency, Central Java. The implementation method in this service uses several things, namely: (1) socialization, (2) education, (3) legal assistance, (4) partner networks. Through this service program, it is hoped that in addition to realizing collaboration between institutions: the Faculty of Law UNNES-LBH-PGRI, it is also hoped that this activity can provide encouragement for teachers in increasing the capacity of legal assistance.